Netflix Advertising for Generation Z. An Analysis of Sex Education and Elite - Cortés Quesada, Jose Antonio; Garcia Rivero, Ainhoa; Fernández Gómez, Erika (Historia y Comunicación Social, 2026)
This paper analyzes Netflix advertising in two series aimed at Generation Z: Sex Education and Elite. The platform, a pioneer in including traditional advertising in spot format, serves as the basis for an exploratory study on advertising techniques, both spots and product placement, aimed at this audience. The objective is to understand the overall advertising exposure of viewers. The ads last less than a minute and product placement is introduced with minimal interruptions to the narrative, moving away from advertising saturation. Netflix is consolidating its position as a platform for brands interested in young audiences, with a predominance of female beauty products, accessories, and shopping centers, reinforcing unsustainable consumption linked to traditional beauty standards that affect young people.